2018
DOI: 10.14776/piv.2018.25.e1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Clinical Correlations of Staphylococcus aureus Discovered in Stools from Children Hospitalized at a Secondary Hospital

Abstract: Purpose: Research on the clinical role of Staphylococcus aureus as a pathogen in acute gastroenteritis (AGE) in children has been scarce. This study aimed to clarify the prevalence and clinical correlation of S. aureus detection in children with AGE. Methods: Fecal samples were collected from children with symptoms of AGE who visited a secondary hospital between January 2012 and December 2015. The samples were sent to the Seoul Metropolitan Government Research Institute of Public Health and Environment to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Since 2015, pathogenic E. coli has been increasingly detected and is the most common, were the most common enterotoxins, whereas SEA (28%) was relatively uncommon, unlike previous studies (64). S. aureus and C. perfringens were the most common bacteria in an infant study (25).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
See 1 more Smart Citation
“…Since 2015, pathogenic E. coli has been increasingly detected and is the most common, were the most common enterotoxins, whereas SEA (28%) was relatively uncommon, unlike previous studies (64). S. aureus and C. perfringens were the most common bacteria in an infant study (25).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…In older children, Campylobacter spp. was the most common [ 64 , 65 ]. In a domestic pediatric staphylococcal food poisoning study, seg (83%) and sei (77%) were the most common enterotoxin genes, whereas sea (28%) was relatively uncommon, unlike previous studies (64).…”
Section: Bacterial Gastroenteritismentioning
confidence: 99%
“…As Staphylococcus aureus also resides on human hands and skin, cross-contamination must be avoided. S. aureus contains 16 types of enterotoxins: SEA, SEB, SEC, SED, SEE, SEG, SEH, SEI, SEJ, SEK, SEL, SEM, SEN, SEO, SEP, and SEQ (Cho et al, 2011;Shin et al, 2018). In the current status of the outbreak of S. aureus, it has been reported that the occurrence of SEA, SEB, SEC, SED, and SEE-toxins is the most common (Cho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%